Analyzing Rhetorical Patterns in Donald Trump’s Speech: A Sociolinguistic Approach - I Komang Artha Wiguna; I Dewa Ayu Devi Maharani Santika (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2025)
Language plays a crucial role in shaping political perception, especially when used strategically through rhetorical devices. Previous studies have often focused on the structural aspects of political language, but many tend to overlook how rhetoric is emotionally received and interpreted by audiences with different ideological backgrounds. This study aims to bridge that gap by examining how Donald Trump’s speeches apply rhetorical appeals of pathos, ethos, and logos, and how these appeals generate different public reactions.This research uses a descriptive qualitative approach that focuses on interpreting meaning and persuasive strategies rather than measuring them numerically. Five major campaign and presidential speeches delivered between 2015 and 2021 were purposively chosen based on their rhetorical importance and audience impact. The data were collected from speech transcripts, audience reactions, and online comments, then analyzed using Herrick’s (2015) rhetorical theory and Garrett’s (2010) language attitude theory. The analysis went through three stages: data reduction, classification of rhetorical appeals, and interpretation of audience responses. The data were examined manually through careful reading and interpretation to maintain consistency and ensure the credibility and replicability of the research.The findings show that emotionally charged expressions trigger strong emotional and behavioral responses from Trump’s supporters, while also provoking skepticism and opposition from his critics. Ethos-based statements strengthen perceived credibility and loyalty even without factual evidence, and logos-based arguments simplify complex political issues into clear and relatable messages that shape public perception. In conclusion, Trump’s rhetorical strategies work not only as persuasive tools but also as means of identity building and ideological polarization. By combining theoretical perspectives and real audience responses, this study highlights political rhetoric as both a linguistic force and a sociocultural influence.